Regole e progetti per il paesaggio Verso il nuovo piano paesaggistico della Toscana - Poli, Daniela (Territori, 2012)
This book brings together the materials of a study carried out by the Florence Faculty of Architecture in liaison with the Tuscan scientific community (five universities, research institutes and technicians from the Regional Authority) to define the methods and approaches of the new Landscape Plan. The aim was to exploit the opportunities offered by recent legislation, such as the European Landscape Convention and the Cultural Heritage and Landscape Code, in order to formulate public policies and projects designed to enhance the quality of life throughout the entire territory, both valuable and degraded. Different skills, aptitudes and passions have come together in the hope that the recent phase of planning can trigger mechanisms that stimulate the inhabitants of Tuscany to continue to produce the collective work of art that is their landscape, in the exquisitely normal manner and form that left scholars such Desplanques pleasantly perplexed when he wrote: «These people have constructed their rural landscapes as if they had no concern other than beauty.»